PERKEMBANGAN MAKNA KATA IRHĀB ‘TERORIS’ DAN JIHĀD ‘JIHAD’ DALAM BAHASA ARAB (Kajian Linguistik Arab Terhadap Peristilahan Radikalisme) - Ardiansyah Ardiansyah (AT-TURATS, 2015)
Language is the most effective communication device and has huge influence for its speaker behavior. The way of thinking, understanding, and radicalism cannot be separated from language. Therefore, this article provides several terms related to radicalism, i.e. irhab ‘terorist’ and ‘jihad’. The terms are analyzed using relevant Arabic linguistic theories. It is the theory of semantic development (ath-thawwur ad-dalaly) that constitutes a part of semantics, one of the linguistics disciplines. This article also discusses the definition of both words irhab and jihad based on linguistics. The definition is also viewed from its periodic language history: pre-Islamic and present. Semantic development in the jahili age can be seen from jahili poem related to the use of the two words. As result, the meanings of these two words have been changing from time to time.